A Review on – Liposomes as a Novel Drug Delivery System (International Journal of Scientific Research in Science and Technology, 2024)
A flexible and promising drug delivery method are liposomes. Site-targeting, delayed or controlled release, protection of medications from degradation and clearance, increased therapeutic effects, and fewer harmful side effects are some of the advantages of liposomes over alternative drug delivery methods. Liposomes offer numerous advantages and applications due to their efficaciousness as drug carriers in pre-clinical and clinical investigations. Furthermore, problems related to liposomal stabilization, effective targeting strategies, and some of their limitations were covered. The development of liposomes has made it possible to alter the way that many medications are biodistributed, which has improved the substances’ medicinal qualities. To sum up, the purpose of this research is to examine the liposomes that are presently available on the market and are employed for a variety of medicinal purposes.